Isolated Left Bundle Branch Block in a Toddler - Hitesh Agrawal; Frank Zimmerman; Zahra Naheed (Case Reports in Cardiology)
Left bundle branch block (LBBB) usually occurs as a postoperative complication from surgical correction of congenital heart disease and can be associated with hypertensive heart disease, coronary artery disease, myocarditis, and aortic valvular disease. Although isolated LBBB is a conduction abnormality found in some healthy adults, it has not been reported in pediatric population. We report a 2-year-old, healthy African American female who was incidentally discovered to have isolated LBBB that has persisted in a follow-up of 3 years.